T128. ATTACHMENT REPRESENTATIONS IN CHILDREN AT FAMILIAL HIGH RISK OF SEVERE MENTAL DISORDERS. ASSOCIATIONS WITH PSYCHOPATHOLOGY, LEVEL OF FUNCTIONING, AND PSYCHOTIC EXPERIENCES. (18th May 2020) - Gregersen, Maja; Ellersgaard, Ditte Vestbjerg; Søndergaard, Anne; Christiani, Camilla; Hemager, Nicoline; Spang, Katrine Søborg; Burton, Birgitte Klee; Uddin, Md Jamal; Ohland, Jessica; Gantriis, Ditte; Greve, Aja; Mors, Ole; et al.
Abstract: Background: There is evidence of higher rates of insecure and disorganized attachment in infancy in children born to parents with severe mental disorders, but evidence on attachment in middle childhood for these children is lacking. This study aims to explore attachment representations in seven-year-old children born to parents with schizophrenia or bipolar disorder. We also aim to explore possible associations between attachment and psychopathology, level of functioning, and psychotic experiences in these children. - We expect that children at familial high risk will have the highest levels of insecure and disorganized attachment. We expect that population based controls will have the lowest levels of insecure and disorganized attachment and higher levels of security than children at familial high risk. - We expect higher levels of insecure and disorganized attachment to be associated with an increased risk of psychopathology, and psychotic experiences and with lower levels of functioning, whereas we expect higher levels of secure attachment to be associated with a lower risk of psychopathology, and psychotic experiences, and with higher levels of functioning. Methods: The Danish High Risk and Resilience Study VIA 7 is a prospective cohort study of 522 seven-year-old children born in Denmark. The cohort consists of children where one or both parents have been diagnosed with a schizophrenia spectrum disorder (N=202), children where one or both parents have been diagnosed with bipolar affective disorder (N=120) and children where neither of the parents have been diagnosed with these disorders (N=200). Attachment representations were assessed with the Story Stem Assessment Protocol whereas psychopathology, level of functioning, and psychotic experiences were assessed with K-SADS. Results: Data analyses are ongoing but preliminary results indicate that there are no significant differences in attachment representations between the three groups of children, but that there are associations between higher rates of insecure and disorganized attachment and a higher risk of psychopathology. Results will be presented at the SIRS-conference. Discussion: Understanding attachment and its correlates in children at familial high risk of severe mental disorders is important in order to strengthen our understanding of developmental trajectories towards mental disorders in these children.